PD-L1 expressing granulomatous reaction as an on-target mechanism of steroid-refractory immune hepatotoxicity. (28th March 2019) - Black, James RM; Goldin, Robert D; Foxton, Matthew; Marafioti, Teresa; Akarca, Ayse U; Pria, Alessia Dalla; Brock, Cathryn; Bower, Mark; Pinato, David J
Immune-related hepatitis is an important toxicity from immune-checkpoint inhibitor therapy, affecting up to 20% of patients on dual cytotoxic T-lymphocyte antigen 4/programmed cell death 1 (CTLA-4/PD-1) inhibitors. The mechanisms underlying this type of drug-induced liver injury are poorly understood. We report the case of a patient with immune-checkpoint inhibitor-related hepatitis where the presence of a diffuse granulomatous, PD-L1-positive infiltrate on liver biopsy correlated with poor response to corticosteroids. Our findings suggest a potential role for activation of the PD-1 pathway within the histiocitic infiltrate as a mechanism of toxicity. Further studies should address the role of macrophages in this patient group characterized by steroid-refractoriness.